2015
DOI: 10.1016/j.ridd.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effortful control in typical and atypical development: Are questionnaires and neuropsychological measures interchangeable? A latent-variable analysis

Abstract: Objective: Effortful control (EC), the self-regulation component of temperament, is traditionally measured using questionnaires. Through the years, several neuropsychological measures originating from the cognitive psychology and the executive function (EF) literature have been introduced in the domain of temperament research to tap EC. Although this is not particularly surprising, given the conceptual overlap between EC and EF, it remains unclear whether EC questionnaires and neuropsychological EF tasks can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 50 publications
0
26
1
Order By: Relevance
“…Previous studies revealed mixed results in Effortful Control, with some studies showing reduced parent-reported levels (De Pauw et al, 2011; Konstantareas & Stewart, 2006; Samyn et al, 2015), and others reporting no differences, or differences only on specific subscales, on self-reports of Effortful Control (Samyn et al, 2015; Schwartz et al, 2009). Interestingly, a previous study found discrepancies between self- and parent-reports of attention problems in children with HFA (Mazefsky et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies revealed mixed results in Effortful Control, with some studies showing reduced parent-reported levels (De Pauw et al, 2011; Konstantareas & Stewart, 2006; Samyn et al, 2015), and others reporting no differences, or differences only on specific subscales, on self-reports of Effortful Control (Samyn et al, 2015; Schwartz et al, 2009). Interestingly, a previous study found discrepancies between self- and parent-reports of attention problems in children with HFA (Mazefsky et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Children were less likely to report attention problems than their parents, which was interpreted as children and adolescents with HFA being unaware of their attention problems, or its impact on their daily functioning. Samyn and colleagues (2015) also proposed that the inconsistency between parent- and self-report may stem from reduced psychometric reliability. However, in the current study children with HFA exhibited comparable, high levels of reliability in their reports of Effortful Control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no formal subgroup analyses have been conducted in ASD based on EF. However, there is a multitude of conflicting evidence on EF dysfunction in ASD, pointing to heterogeneity in EF skills in this clinical population1516. One consistent finding is more severe EF impairment in ASD than ADHD8131718.…”
mentioning
confidence: 99%
“…While the Diagnostic and Statistical Manual (DSM-523) considers ASD and ADHD to be distinct disorders, there is inadequate construct validity for these disorders based on EF81716. The few studies that have examined specific EF profiles in ASD and ADHD employed variable-centered approaches817 (e.g., group averages), ignoring the heterogeneity within diagnostic categories.…”
mentioning
confidence: 99%